2020
DOI: 10.18203/2394-6040.ijcmph20204752
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the knowledge, attitudes and practices regarding COVID-19 and homoeopathy among the citizens of Delhi and national capital region, India: a cross-sectional online survey

Abstract: Background: Delhi and NCR of India is densely populated with access to an integrated health care delivery system, with a promoted preventive homoeopathic medicine for flu like illnesses. To assess knowledge, attitudes and practices to this unanticipated situation and infectious disease pandemic of COVID-19 continues to be a global and public health challenge.Methods: A survey was conducted. An online cross-sectional survey was conducted in a sample of the residents of Delhi and NCR using a self-prepared pilot-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Knowledge is a prerequisite for adopting a protective mentality and behavior toward a prevalent illness. Studies from around the world indicate that mere knowledge of a disease does not influence the population’s attitudes or behaviors ( Saqlain et al, 2020 ; Shi et al., 2020 ; Suvvari et al, 2021 ; Wadhwani et al, 2020 ). In addition, despite adequate knowledge, the attitude was not always positive, necessitating additional education to explain the importance of developing a positive attitude and engaging in ongoing preventative practices aimed at reducing the incidence of HIV infection and transmission ( Nwagbara et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Knowledge is a prerequisite for adopting a protective mentality and behavior toward a prevalent illness. Studies from around the world indicate that mere knowledge of a disease does not influence the population’s attitudes or behaviors ( Saqlain et al, 2020 ; Shi et al., 2020 ; Suvvari et al, 2021 ; Wadhwani et al, 2020 ). In addition, despite adequate knowledge, the attitude was not always positive, necessitating additional education to explain the importance of developing a positive attitude and engaging in ongoing preventative practices aimed at reducing the incidence of HIV infection and transmission ( Nwagbara et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Such confusion was also revealed about the requirement for hospitalization in each case. It was understandable that studies conducted during the early phase of the lockdown also showed such a lack of knowledge ( Wadhwani et al, 2020 ). At that time, even the medical personnel and hospitals were unclear about their roles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, data collection of COVID-19 cases in various projects worldwide showed that only a few medicines were frequently used. 1 2 3 4 5 6 These medicines were: Arsenicum album (Ars) , Belladonna (Bell) , Bryonia (Bry) , Gelsemium (Gels) , Hepar sulphuris (Hep) , Magnesia muriatica (Mag-m) , Nux vomica (Nux-v) , Phosphorus (Phos), and Pulsatilla (Puls) . Some other medicines, such as Mercurius solubilis (Merc) , were used by a specific group of doctors but by few others.…”
Section: Introductionmentioning
confidence: 99%